Assessing Student Teachersâ Performance in English Class Through Teaching Video - Rokhayani, Atik (Sebelas Maret University, 2016)
Student teachers are students who are prepared to be teachers. They will be the professional English teachers in the future. So, before graduating from university, they must be prepared to be able to teach English well. Creating and managing English class are important things since they are in the English Education Department. Furthermore, the use of Classroom English and variation of teaching are the main points need to be considered. Teaching Practice Program is a program for student teachers in transferring the theory they got from university to be applied at schools. Teaching to the real students will be challenging for them. So, they need a good preparation before performing in front of the class. In fact, there are many studentsâ teacher still not confident when they are teaching. Some difficulties face by them related to teaching learning process. Teaching video is one of the techniques in assessing student teachersâ performance to reduce the problem face by them. This paper explores the student teachersâ variation in conducting teaching practice at schools. The student teachers are asked to record their performance while doing teaching practice program. The writer investigates their performance in teaching to the real students. The use of teaching video can be used as a reflective teaching to improve student teachersâ performance in English class.